Ling-gui-zhu-gan promotes adipocytes browning via targeting the miR-27b/PRDM16 pathway in 3T3-L1 cells - Ye, Zimengwei; Zhao, Yi; Cui, Yanjing; Xu, Bingrui; Wang, Fan; Zhao, Dandan; Dong, Guangtong; Wang, Zhufeng; Wu, Rui (Frontiers in Pharmacology, 2024)
Introduction: Obesity, a global epidemic, is caused by an imbalance between energy intake and expenditure. The induction of white adipose browning to increase heat production has emerged as a potential effective strategy to address obesity. Ling-gui-zhu-gan (LGZG), a traditional Chinese medicine formula, has been proved to achieve promising results to combat obesity and related metabolic diseases, yet the mechanisms remain largely unexplored. This study aimed to elucidate the anti-obesity properties and the mechanisms of LGZG by investigating its browning effect on 3T3-L1 adipocytes. Methods: LGZG-containing serum obtained by oral administration of LGZG to animals was added to 3T3-L1 adipocytes to simulate in vivo conditions. Results: The results showed that 49 compounds were identified in LGZG-containing serum by UHPLC-Q-Orbitrap HRMS, including compounds such as atractylenolides and polyporenic acid C, etc. LGZG-containing serum alleviated the lipid accumulation and decreased both intracellular and extracellular triglyceride contents in a dose-dependent manner. This reduction is accompanied by enhanced mitochondrial respiratory and heat production function. Mechanistically, LGZG-containing serum led to a decrease in miR-27b expression and an increase in the mRNA and protein levels of browning-related markers, including UCP1, PRDM16, PGC-1α, PPARγ, CTBP1, and CTBP2. Further investigation using miR-27b mimic transfection confirmed that miR-27b/PRDM16 pathway might be a potential mechanism by which LGZG-containing serum promotes browning of 3T3-L1 adipocytes. Discussion: These results underscore the therapeutic potential of LGZG in addressing obesity and its associated metabolic disorders through the promotion of adipose browning.